2014
DOI: 10.3389/fimmu.2014.00158
|View full text |Cite
|
Sign up to set email alerts
|

Organizing MHC Class II Presentation

Abstract: Major histocompatibility complex (MHC) class II molecules are ligands for CD4+ T cells and are critical for initiating the adaptive immune response. This review is focused on what is currently known about MHC class II organization at the plasma membrane of antigen presenting cells and how this affects antigen presentation to T cells. The organization and diffusion of class II molecules have been measured by a variety of biochemical and microscopic techniques. Membrane lipids and other proteins have been implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Consistent with these observations, deletion of the cytoplasmic tail increased the lateral mobility of MHCI (43). Clustering of MHCII complexes on the plasma membrane of APCs has also been reported (44)(45)(46). Using SPT approaches, it was shown that MHCII displays hop diffusion on the cell membrane in a manner that it is dependent on the integrity of the actin cytoskeleton (47).…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with these observations, deletion of the cytoplasmic tail increased the lateral mobility of MHCI (43). Clustering of MHCII complexes on the plasma membrane of APCs has also been reported (44)(45)(46). Using SPT approaches, it was shown that MHCII displays hop diffusion on the cell membrane in a manner that it is dependent on the integrity of the actin cytoskeleton (47).…”
Section: Discussionsupporting
confidence: 60%
“…Spatial arrangement of TCRs and their pMHC ligands and assembly into organized structures has been suggested to play a decisive role in this 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Creation of chemical contrast by e-beam This is especially true for peptide-MHC class I. Much less is know about MHC class II 18 . lithography, which is subsequently used to recruit the relevant proteins, is an option but is limited due to its high cost.…”
Section: Introductionmentioning
confidence: 99%